Amoeba Genome Reveals Dominant Host Contribution to Plastid Endosymbiosis. (13th August 2020) - Lhee, Duckhyun; Lee, JunMo; Ettahi, Khaoula; Cho, Chung Hyun; Ha, Ji-San; Chan, Ya-Fan; Zelzion, Udi; Stephens, Timothy G; Price, Dana C; Gabr, Arwa; Nowack, Eva C M; Bhattacharya, Debashish; et al.
Abstract: Eukaryotic photosynthetic organelles, plastids, are the powerhouses of many aquatic and terrestrial ecosystems. The canonical plastid in algae and plants originated >1 Ga and therefore offers limited insights into the initial stages of organelle evolution. To address this issue, we focus here on the photosynthetic amoeba Paulinella micropora strain KR01 (hereafter, KR01) that underwent a more recent (∼124 Ma) primary endosymbiosis, resulting in a photosynthetic organelle termed the chromatophore. Analysis of genomic and transcriptomic data resulted in a high-quality draft assembly of size 707 Mb and 32, 361 predicted gene models. A total of 291 chromatophore-targeted proteins were predicted in silico, 208 of which comprise the ancestral organelle proteome in photosynthetic Paulinella species with functions, among others, in nucleotide metabolism and oxidative stress response. Gene coexpression analysis identified networks containing known high light stress response genes as well as a variety of genes of unknown function ("dark" genes). We characterized diurnally rhythmic genes in this species and found that over 49% are dark. It was recently hypothesized that large double-stranded DNA viruses may have driven gene transfer to the nucleus in Paulinella and facilitated endosymbiosis. Our analyses do not support this idea, but rather suggest that these viruses in the KR01 and closely related P. micropora MYN1 genomes resulted from a more recent invasion.